Genotype-dependent regulation of vitamin E biosynthesis in olive fruits as revealed through metabolic and transcriptional profiles - Georgiadou, Egli C.; Koubouris, Georgios; Goulas, Vlasios; Sergentani, Chrysi K.; Nikoloudakis, Nikolaos; Manganaris, George A.; Kalaitzis, Panagiotis; Fotopoulos, Vasileios (My University, 2019)
Vitamin E is a general term used to describe a group of eight lipophilic compounds known as tocochromanols. These vitamin E variants are chemically categorised into two classes formed by α-, β-, γ- and δ- tocopherols and tocotrienols isoforms, respectively. The present study describes the concurrent regulation of genes and metabolites orchestrating vitamin E biosynthesis in olive drupes of five distinctive Greek olive cultivars. A combination of analytical, biochemical and molecular approaches was employed in order to carry out comparative analyses, including real-time RT-qPCR for gene expression levels and HPLC analysis of metabolite content. Findings indicated that tocochromanol levels and composition, oil content, gene expression levels as well as total antioxidant activity were highly dependent on cultivar and, to a lesser extent, on fruit developmental stage. Specifically, cultivars 'Kalokairida' and 'Lianolia Kerkyras' demonstrated the highest vitamin E content. The latter possessed high tocochromanol content combined with highest overall antioxidant activity in all developmental stages, concomitant with the up-regulation expression profile of HPPD. The genotypic imprint versus the temporal contribution to vitamin E levels, as well as the potential link to lipid peroxidation amelioration, are discussed.
Keywords: Gene expression; Oil content; Olea europaea L.; tocochromanols; α-tocopherol